2015
DOI: 10.5536/kjps.2015.42.4.327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chicken Feet Gelatin on Physicochemical and Sensory Properties of Restructured Chicken Jerky

Abstract: This study aimed to investigate the effect of chicken feet gelatin on physicochemical and sensory properties of restructured chicken jerky. Chicken feet swollen with hydrochloric solution (0.1 N HCl) were neutralized with flowing tap water, and gelatin was extracted with hot water at 75℃. The obtained chicken feet gelatin was dehydrated via freeze-drying. Restructured chicken jerky samples were prepared by adding the following amount of chicken feet gelatin 0%, 1%, 2%, 3%. The moisture and protein content of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(6 reference statements)
0
3
0
1
Order By: Relevance
“…식육자원 중 닭고기는 백색육으로 스킨을 제외한 단백질 함량과 지방함량이 각각 20%와 5%로 대표적인 저지방 고 단백식품이다 (Bonoli et al, 2007, Hwang et al, 2014, Kim et al, 2015a. 1인당 닭고기 소비량은 2012년 기준 1980년 대보다 300% 상승하여 돼지고기, 소고기 소비증가율보다 높은 증가율을 보이며 (Korea Poultry Association, 2015), 일 반적으로 프라이드치킨, 스모크치킨, 삼계탕, 닭갈비, 닭고기 너겟 등 다양하게 가공되어 소비된다.…”
Section: 서 론unclassified
“…식육자원 중 닭고기는 백색육으로 스킨을 제외한 단백질 함량과 지방함량이 각각 20%와 5%로 대표적인 저지방 고 단백식품이다 (Bonoli et al, 2007, Hwang et al, 2014, Kim et al, 2015a. 1인당 닭고기 소비량은 2012년 기준 1980년 대보다 300% 상승하여 돼지고기, 소고기 소비증가율보다 높은 증가율을 보이며 (Korea Poultry Association, 2015), 일 반적으로 프라이드치킨, 스모크치킨, 삼계탕, 닭갈비, 닭고기 너겟 등 다양하게 가공되어 소비된다.…”
Section: 서 론unclassified
“…The pH values of semi-dried restructured jerky significantly ( p < 0.05) increased with an increase in duck skin gelatin concentration and the addition of carrageenan. Both according to Kim et al [ 17 ], the process of pH adjustment during gelatin neutralization affects the product. In the present study, the addition of duck skin gelatin neutralized to pH 7 affected the pH of the semi-dried restructured jerky.…”
Section: Resultsmentioning
confidence: 99%
“…The flavor, texture, and overall acceptability scores were the highest ( p < 0.05) for the G1C group ( Table 4 ). Several researchers reported that the texture property of jerky is the most important sensory attribute [ 2 , 8 , 17 , 29 ]. Kim et al [ 29 ] found that semi-dried jerky showed an increase in tenderness score with an increase in the addition of chicken feet gelatin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation